Hukum Relokasi Bangunan Masjid ke Atas Tanah Kuburan: Analisis Fikih Islam, Fatwa Kontemporer dan Relevansinya dengan Hukum Positif Indonesia - Febriyani Febriyani; Husna Karimah; Marhadi Muhayar (Al-Wasathiyah: Journal of Islamic Studies, 2026)
This study examines the legal status of mosque relocation onto former cemetery land through a comparative analysis of the views of the four Sunni schools of Islamic jurisprudence, contemporary religious fatwas, and Indonesian positive law. The study is motivated by the growing need to relocate or construct mosques on land previously used as burial grounds, which raises legal issues concerning respect for the deceased, the status of waqf property, and the prohibition of turning graves into places of worship. This research employs a normative legal method using comparative fiqh (muqāranah al-madhāhib), fatwa analysis, and a statutory approach. The findings indicate that the majority of scholars from the four madhhabs prohibit or regard as reprehensible the construction of mosques over graves due to the potential for grave veneration and the violation of the sanctity of places of worship. The Hanafi, Maliki, and Shafi‘i schools emphasize preventing excessive reverence toward graves, while the Hanbali school permits the use of former cemetery land after the remains have been relocated in accordance with Islamic law. The Indonesian Council of Ulama (MUI) allows relocation through the mechanism of waqf substitution (istibdal) for the sake of public benefit, whereas Dar al-Ifta’ of Egypt and the Saudi Permanent Committee (Lajnah Dā’imah) adopt different approaches regarding the presence of graves within mosque premises. This study concludes that mosque relocation to former cemetery land may be permissible provided that the graves are relocated according to Islamic legal requirements, the legal status of the land is properly resolved, and greater public benefit can be achieved.